Effects of Crude Oil Contamination on Seeds Germination and Growth of Arachis Hypogea and Citrullus Vulgaris - I. U., Ubong,; Reapson, Sunday, A. E. (RA Journal Of Applied Research, 2018)
The effects of crude oil contamination on the germination, and growth of groundnut (Arachis hypogea L.) and egusi melon (Citrullus vulgaris L.) were investigated in a green house under control environmental condition. Planting was done in a wide open black polythene bag filled with 10kg of 2mm sieved soil. Eight polythene bags, each per crude oil concentration were used (four polythene bags for groundnut and four for egusi melon). Treatment of the soil was carried out by adding varying concentration of crude oil raging from 0, 0.5, 2 and 5% into soil sample content in the polythene bag. Each concentration of crude oil was added to each soil sample in each bag ( four bags for groundnut and four bags for egusi melon) and was thoroughly mixed using gloved hands. Seeds of groundnut ( Arachis hypogeal L.) were planted into each of the four polythene bags with soil sample treated with varying concentration of crude oil and Seeds of Egusi melon (Citrullus vulgaris L.) were planted to each of the other four polythene bags of soil sample treated with vary concentration of crude oil. The result indicated that crude oil pollution of 2 and 5% significantly reduced the germination and growth of the Citrullus vulgaris (melon) while in Arachis hypogeal (groundnuts), germination increased with increase in crude oil contamination of up to 5%. At 5% oil level, all the seeds of groundnut germinated but with time there was a reduction in the growth parameters possibly due to the coagulatory effect of increasing crude oil on the soil binding the soil particles into water impregnable soil block which impaired water drainage and oxygen diffusion. Also the tolerance exhibited by groundnuts could possibly be linked to its ability to fix nitrogen.